2004
DOI: 10.1002/hep.20044
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of cerebral hyperemia by the administration of terlipressin in acute liver failure with severe encephalopathy

Abstract: There is increasing evidence that terlipressin is useful in patients with cirrhosis and hepatorenal syndrome, but there are no data of its use in patients with acute liver failure (ALF) in whom hepatorenal syndrome is common. Although terlipressin produces systemic vasoconstriction, it produces cerebral vasodilatation and may increase cerebral blood flow (CBF). Increased CBF contributes to intracranial hypertension in patients with ALF. The aim of this study was to evaluate the safety of terlipressin in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 34 publications
(28 reference statements)
0
50
1
1
Order By: Relevance
“…This has not been made as most patients with HRS being in the waiting list for LT are frequently treated with vasopressin analogues or other vasoconstrictors because of the potential efficacy of treatment and the absence of alternative therapies. Other factors hampering the use of terlipressin (or other vasoconstrictors) for HRS include the concern that vasoconstrictor therapy may be complicated by important side-effects, 29 and their use is not recommended in patients with cardiac diseases, peripheral vascular and cerebrovascular diseases because of the potential risk of ischaemic events. These complications occurred with ornipressin that was soon abandoned; [5][6] although one of the initial concerns about terlipressin use was the development of ischaemia, no patient of the current review interrupted the terlipressin therapy because of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…This has not been made as most patients with HRS being in the waiting list for LT are frequently treated with vasopressin analogues or other vasoconstrictors because of the potential efficacy of treatment and the absence of alternative therapies. Other factors hampering the use of terlipressin (or other vasoconstrictors) for HRS include the concern that vasoconstrictor therapy may be complicated by important side-effects, 29 and their use is not recommended in patients with cardiac diseases, peripheral vascular and cerebrovascular diseases because of the potential risk of ischaemic events. These complications occurred with ornipressin that was soon abandoned; [5][6] although one of the initial concerns about terlipressin use was the development of ischaemia, no patient of the current review interrupted the terlipressin therapy because of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine is the preferred agent; however, more recently the vasopressin analogue terlipressin has been used in ALF with conflicting results [24] [25]. For the reasons mentioned, patients with ALF require invasive hemodynamic monitoring.…”
Section: Intensive Carementioning
confidence: 99%
“…Two important clinical studies in this issue of HEPATOLOGY deal with these topics. 3,4 Terlipressin is a vasopressin analog that is increasingly used to reverse hepatorenal syndrome in patients with chronic liver disease. Renal failure also is common in FHF, and the value of terlipressin to prevent or treat renal failure is of considerable interest.…”
mentioning
confidence: 99%
“…Renal failure also is common in FHF, and the value of terlipressin to prevent or treat renal failure is of considerable interest. Before launching a randomized controlled trial, Shawcross et al 3 carried out an important safety study, reported in this issue of HEPATOL-OGY at the Scottish Liver Transplant Unit in Edinburgh that included six patients with FHF. Both CBF and ICP were recorded before and after intravenous injection of a minimal dose of terlipressin that did not affect systemic hemodynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation